Nephroprotective effect of Dapsone against Gentamicin-Induced Acute Nephrotoxicity in Rats - Hussein, Uday Abdul-Reda; M. Mohammed , Naseer; F Al-Saedi, Haider; A Ramadhan, Mukhallad (Iraqi Journal of Pharmaceutical Sciences, 2024)
Nephrotoxicity is one of the major complications and clinical limitations of gentamicin. This study aimed to evaluate the nephroprotective effect of dapsone against gentamycin-induced nephrotoxicity in rats.Twenty-four healthy rats weighing between (270-300) g were equally divided into three groups, eight rats in each group: control group received normal saline (2mL/kg/day I.P.) for 10 days , gentamicin group received (100 mg/kg/day I.P.) for 10 days, and dapsone group received (5 mg/kg/day p.o) concomitantly with gentamicin (100 mg/kg/day I.P.) for 10 days. At the end of experiment, blood and kidney tissue samples were collected from all animals for biochemical and histopathological examination.Dapsone exhibited nephroprotective effect manifested by a significant decrease in serum levels of BUN, creatinine and KIM-1 with a significant increase total protein serum level. Besides, it improves oxidative and inflammatory biomarkers of tissues, which was demonstrated by improving histological changes when compared to the gentamicin group. In conclusion, dapsone has a nephroprotective effect by counteracting the renal deleterious effect of gentamicin .